FACTORS RELATED TO COMPLIANCE WITH USING PERSONAL PROTECTIVE EQUIPMENT FOR PESTICIDE SPRAYING FARMERS IN GAMPONG MEUNASAH BLANG PEUDADA BIREUEN - Putri, Hasdiani; Santi, Tahara Dilla; Zulkifli, Zulkifli (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2023)
Background: Spraying pesticides that do not comply with regulations will result in many impacts, including health impacts for humans, namely poisoning farmers. In Aceh Province, there were 612 cases of pesticide poisoning in 2014 in various regions. This research aims to determine the factors related to compliance with using Personal Protective Equipment (PPE) among pesticide spraying farmers in Gampong Meunasah Blang Peudada Bireuen. Method: This research uses descriptive analytical methods with a crosssectional design. The population in this study were all pesticide spraying farmers in Gampong Meunasah Blang Bireuen. The sample is a total population of 46farmers. Data collection was carried out for 12 days from 1 to 12 January 2019 using questionnaires and interviews. Data analysis used the Chi-Square test with the SPSS computer program. Result: Univariate research shows farmers who do not comply with using PPE (69.6%), poor knowledge (65.2%), negative attitudes (54.3%), secondary education level (43.5%), and medium length of work (50 %). The results of bivariate research show that there is a relationship between knowledge (p=0.03) and attitude (p=0.02) with compliance with using PPE among farmers. However, there was no significant relationship between education (p=0.20) and length of service (p=0.69) with compliance in using PPE among farmers. Recommendation: It is hoped that the Agricultural Extension Center can provide training to farmers on how to use PPE correctly when spraying pesticides and can provide education regarding the magnitude of the effects and dangers of using pesticides incorrectly.